2014
DOI: 10.2527/jas.2013-7453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum 2142 and sodium n-butyrate in lipopolysaccharide-triggered inflammation: Comparison of a porcine intestinal epithelial cell line and primary hepatocyte monocultures with a porcine enterohepatic co-culture system12

Abstract: This study was based on our previously developed double-layered enterohepatic co-culture system, composed of nontumorigenic porcine intestinal epithelial cell line (IPEC-J2) and primary culture of porcine hepatocytes. The anti-inflammatory effect of spent culture supernatant of Lactobacillus plantarum 2142 (Lp2142; 13.3%) and sodium n-butyrate (2 mM) was tested on IPEC-J2 and hepatocyte monocultures as well as on the gut-liver co-culture. To mimic inflammation, lipopolysaccharide (LPS; 1 and 10 μg/mL) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…In our previous works, secreted bioactive metabolites of lactobacilli were proved to be effective in the treatment of intestinal inflammation on in vitro intestinal models [15,16]. We demonstrated that spent culture supernatant (13.3%) of Lp 2142 was effective in decreasing IL-8 and TNF-α mRNA level in IPEC-J2 cultures after LPS treatment.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our previous works, secreted bioactive metabolites of lactobacilli were proved to be effective in the treatment of intestinal inflammation on in vitro intestinal models [15,16]. We demonstrated that spent culture supernatant (13.3%) of Lp 2142 was effective in decreasing IL-8 and TNF-α mRNA level in IPEC-J2 cultures after LPS treatment.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, chlorogenic acid is not reported to have significant bioavailability until it reaches the colon, where the microbiota rapidly hydrolyses it to liberate caffeic acid [9]. Metabolites of probiotic bacteria also have a proven anti-inflammatory effect [15,16]. Furthermore, unabsorbed polyphenols in the colon could influence the constitution and quality of microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Although LPS-dose and -type were comparable to our study, there were differences in IPEC-J2 culture conditions -impermeable supports vs. permeable supports in our study -and possibly in cell culture passages as well as a shorter incubation time for LPS that might have contributed to the apparent differences. Others used a short-term Salmonella-LPS challenge (1 h) in an IPEC-J2 model grown on inserts and reported an upregulation of IL-8 transcripts (Farkas et al, 2015) and a slight increase in IL-8 protein production to the basolateral site (Farkas et al, 2014). In these studies IPEC-J2 were cultured in the presence of antibiotics and challenged with a different type of LPS.…”
Section: Discussionmentioning
confidence: 98%
“…The ability of specified microbiome lactobacilli to metabolize polyphenols found in certain fruits (16) or fermented soy (8), which work in concert with SCFAs such as butyrate (10, 20) to enhance muscle oxidative capacity by stimulating mitochondria, can potentially be exploited to produce a form of metabolic stabilization somewhat reminiscent of that exerted by physical activity. Finally, as advanced age is associated with both muscle loss (sarcopenia) and microbiome dybiosis, such a therapeutic approach holds the potential of slowing the onset of several metabolic and structural deficits inflicted by aging in elderly people.…”
Section: Perspectivementioning
confidence: 99%